Coativação linguística durante a leitura de palavras por surdos bilíngues em português brasileiro-libras - Bastos, Ana Paula Rodrigues (2021)
The present study analyzed the phenomenon of linguistic coactivation in bilingualism between an oral language (Brazilian Portuguese - BP) in written form and a sign language – visual-spatial (Libras). A systematic review was conducted to explore the studies published in the last decade (2010-2020) to verify cross-linguistic activation in deaf bilinguals during word reading. Six experimental studies were selected from database search with the descriptors "deaf*" AND "bilingual" NOT cochlear. Four of the studies found adopted as experimental method a task with an implicit semantic judgment paradigm proposed by Thierry and Wu (2007), while the other two used electroencephalogram (EEG) and Event-Related Potentials (ERP). The results of the experiments converge in evidence that signs are activated during written words reading by bilingual deaf people. In this study, to verify the occurrence of linguistic coactivation in the Libras-BP linguistic pair, an experimental task was constructed based on the semantic paradigm used by Morford et al. (2011; 2014), composed of 80 pairs of words written in BP. The participants judged whether there was or not a semantic relationship between the pairs presented. An implicit condition of phonological similarity in Libras was manipulated, which generated four stimulus conditions: semantically related and phonologically similar, semantically unrelated and phonologically similar, semantically related and phonologically distinct and, finally, semantically unrelated and phonologically distinct. Five deaf bilingual adults in Libras and BP and five hearing adults who used BP as their first language, as a control group, participated in the experiment. The participants of the deaf group presented longer response time and lower accuracy in conditions that were not convergent in semantic relation and phonological similarity in comparison with the control group. The results point to the coactivation of signs during reading processing in BP, indicating the occurrence of facilitatory and inhibitory effects resulting from non-select activation of languages, even in different modalities (oral and visualspatial).